1996
DOI: 10.1002/stem.140351
|View full text |Cite
|
Sign up to set email alerts
|

2′,2′‐Difluorodeoxycytidine (Gemcitabine) Induces Apoptosis in Myeloma Cell Lines Resistant to Steroids and 2‐Chlorodeoxyadenosine (2‐CdA)

Abstract: Abstract. The paucity of effective cytotoxic agents for the treatment of steroid resistant multiple myeloma explains the ongoing search for alternative substances for chemotherapy of this disease. In the present study, the purine antagonist 2-chlorodeoxyadenosine (2-CdA, cladribine) and the pyrimidine antagonist 2′,2′-difluorodeoxycytidine (gemcitabine) were tested on four myeloma cell lines (i.e., U 266, OPM 2, RPMI 8226, IM 9), one plasma cell leukemia cell line (HS Sultan) and a myeloid control cell line (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Gemcitabine has potent activity against myeloma cell lines in vitro, including cells resistant to other drugs. [46,47] Unfortunately, gemcitabine has not been adequately tested clinically in this disease. In a small phase 2 trial of weekly 30-minute infusions little activity was observed against refractory tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine has potent activity against myeloma cell lines in vitro, including cells resistant to other drugs. [46,47] Unfortunately, gemcitabine has not been adequately tested clinically in this disease. In a small phase 2 trial of weekly 30-minute infusions little activity was observed against refractory tumors.…”
Section: Discussionmentioning
confidence: 99%
“…1% Triton X-100) for permeabilization and DNA staining. Analysis of cell size and fluorescence intensity was performed in the forward/side scatter program of a Becton Dickinson FACScan as recently described in detail (Nicoletti et al, 1991;Gruber et al, 1996). After exclusion of necrotic debris, apoptotic cells in PI-assays were defined by a decrease in DNA content as compared to G1 phase cells of myeloma cell lines and normal T lymphocytes.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from 1 × 10 7 cells, using phenol-chloroform and then electrophoretically separated in a 1 . 8% agarose gel, as described previously (Gruber et al, 1996). Cell pellets were resuspended in 100 ml ice-cold PBS/EDTA, to which 900 ml of lysis buffer (0 .…”
Section: Methodsmentioning
confidence: 99%
“…On CML cells, gemcitabine was demonstrated to be more effective than the nucleoside analog cladribine [117]. Gemcitabine induces apoptosis in myeloma and plasma cell leukemia lines resistant to steroids and cladribine [119]. Gemcitabine induces apoptosis in myeloma and plasma cell leukemia lines resistant to steroids and cladribine [119].…”
Section: Gemcitabinementioning
confidence: 99%